2006
DOI: 10.1158/1055-9965.epi-06-0291
|View full text |Cite
|
Sign up to set email alerts
|

Association of Polymorphisms in AhR, CYP1A1, GSTM1, and GSTT1 Genes with Levels of DNA Damage in Peripheral Blood Lymphocytes among Coke-Oven Workers

Abstract: Accumulating evidence has shown that both DNA damage caused by the metabolites of polycyclic aromatic hydrocarbons (PAH) and genetic polymorphisms in PAH-metabolic genes contribute to individual susceptibility to PAH-induced carcinogenesis. However, the functional relevance of genetic polymorphisms in PAH-metabolic genes in exposed individuals is still unclear. In this study of 240 coke-oven workers (the exposed group) and 123 non -coke-oven workers (the control group), we genotyped for polymorphisms in the Ah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 35 publications
2
15
1
1
Order By: Relevance
“…Further, the metabolism of PAHs induces DNA damage and carcinogenesis which could be modulated by genetic variation (Shimizu et al, 2000;Jiang et al, 2005;Ramadoss et al, 2005;Chen et al, 2006). In this study, significant difference (p=0.02, 95%CI, 0.70-15.86) was observed in the R273G mutation in p53 exon 8 for the genetic polymorphisms of Lys/Arg for AhR.…”
Section: 2699 Impact Of Ahr Cyp1a1 Gstm1 Snps On Tp53 R273g Mutatimentioning
confidence: 51%
See 3 more Smart Citations
“…Further, the metabolism of PAHs induces DNA damage and carcinogenesis which could be modulated by genetic variation (Shimizu et al, 2000;Jiang et al, 2005;Ramadoss et al, 2005;Chen et al, 2006). In this study, significant difference (p=0.02, 95%CI, 0.70-15.86) was observed in the R273G mutation in p53 exon 8 for the genetic polymorphisms of Lys/Arg for AhR.…”
Section: 2699 Impact Of Ahr Cyp1a1 Gstm1 Snps On Tp53 R273g Mutatimentioning
confidence: 51%
“…CYP1A1 is the most potently induced gene following AHR activation. The homozygous deletion of GSTM1 leads to the loss of GSTM1 functions (Nerurkar et al, 2000;Chen et al, 2006;Moretti et al, 2007). Therefore, the results indicated that the functions of AhR, CYP1A1 and GSTM1 were more impaired or modified with higher PAH exposure.…”
Section: 2699 Impact Of Ahr Cyp1a1 Gstm1 Snps On Tp53 R273g Mutatimentioning
confidence: 93%
See 2 more Smart Citations
“…Therefore, it is reasonable to hypothesize that genetic polymorphisms of CYP1A1 may play a role in individual susceptibility to genetic damage and developing various types of cancers. The CYP1A1 gene polymorphisms were examined extensively to evaluate the possible role they play in DNA damage and cancer promotion in PAHs exposed populations (Chen et al, 2006;Moretti et al, 2007). Coal-tar workers, working at coal-tar melting and road construction sites, are poorly characterized regarding the CYP1A1 gene polymorphisms as a modulator of genetic damage.…”
Section: Introductionmentioning
confidence: 99%